2007
DOI: 10.1624/105812407x170680
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceptions of Parenting Among Adolescent Mothers

Abstract: Using a descriptive correlational design, this study examined factors that contribute to self-perceptions of parenting among adolescent mothers 4 to 6 weeks postpartum. Healthy, first-time, 13-to 19-year-old adolescent mothers (n ¼ 126) identified their own mothers as their primary source for social support. Additionally, the more tangible the support from the adolescent's mother, the lower the evaluation of self-perceptions of parenting. Older, more educated adolescent mothers were more positive in self-perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 18 publications
7
38
1
Order By: Relevance
“…Adolescent mothers in my preliminary study identified their own mother as a consistent, dependable source of emotional support that positively influenced their self-perceptions of parenting (DeVito, 2007). The more emotional support the adolescents received Adolescent mothers are faced with the dual challenge of progressing through the stages of adolescence and, at the same time, adapting to the maternal role.…”
Section: Selected Findings From the Preliminary Studymentioning
confidence: 96%
See 3 more Smart Citations
“…Adolescent mothers in my preliminary study identified their own mother as a consistent, dependable source of emotional support that positively influenced their self-perceptions of parenting (DeVito, 2007). The more emotional support the adolescents received Adolescent mothers are faced with the dual challenge of progressing through the stages of adolescence and, at the same time, adapting to the maternal role.…”
Section: Selected Findings From the Preliminary Studymentioning
confidence: 96%
“…Their ability to adjust to the role of being a new mother is often influenced by characteristics associated with their particular stage of adolescence. For example, a young mother in the early stage of adolescence still needs to be ''mothered'' by her own mother or a person in her life who acts as her mother (DeVito, 2007;Mercer, 1995Mercer, , 2004. Adolescent mothers, therefore, have specific needs for help to successfully navigate through the combined demands of adolescent development and their role as a new parent.…”
Section: Background Information Parenthood and Adolescent Mothersmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluating the outcomes as a group in need of prenatal education services; the goal was to decrease the rates of child abuse and neglect in this population. The center's targeted group of pregnant teenagers often does not attend regularly scheduled prenatal education classes (DeVito, 2007), so the center developed a series of classes implemented in the teens' school setting to allow them to attend in a location and at a time convenient to them. Other potential groups in the childbirth educator's community could be recent immigrants or specific ethnic or religious minority groups who may have language and cultural barriers to obtaining childbirth education classes.…”
Section: Establishing the Needmentioning
confidence: 99%